Ancient Greece and beyond [videorecording (DVD)] (Secrets of archaeology., 2012)
Explore the ancient cities of Greece, the magnificent temples, the ruins of the Greek Islands, and the influence of the Greek culture throughout the region. Includes state-of-the-art computer graphics, spectacular on-location photography, and research from the world's leading archaeologists. Originally aired on The History Channel.